Association of characters for yield and yield components in soybean [(Glycine max (L.) Merrill)]: Association of characters for yield and yield components in soybean [(Glycine max (L.) Merrill)] - V T NAGARGOJE; M V DHUPPE; K H PATIL (Journal of Oilseeds Research, 2020)
To study genetic association of character for yield and yield components over different environments, 20 soybean genotypes and 5 checks were evaluated in a RBD with three replications during kharif 2014 at three environments. Data were recorded on 10 characters. Significant negative association was observed between seed yield and days to 50% flowering at genotypic and phenotypic level whereas positive correlation was observed between seed yield and 100-seed weight.